+0  
 
0
108
1
avatar

Please help, thanks.

 

 Oct 29, 2018
 #1
avatar+17331 
+1

For quadratic Formula

\(x = {-b \pm \sqrt{b^2-4ac} \over 2a}\)

 

a = 3  b=-12 and c = -663

 

You can simplify the math.....and maybe see 'in your mind' if you can factor it by first dividing the left and right sides of the equation by 3 to get

x^2 - 4x - 221 =0

     Doesn't help me much

        use the QF 

            a = 1 b= -4 c= -221  

 

4+-sqrt(16-4(1)(-221)   /  2   =     4+- 30   /  2   ========>   17    or   -13

 

SO factoring would look like    (x-17)(x+13) = 0

 Oct 29, 2018

19 Online Users

avatar
avatar
avatar
avatar